Copper metallothioneins. Issue 4 (13th March 2017) - Calvo, Jenifer; Jung, Hunmin; Meloni, Gabriele
Abstract: Metallothioneins (MTs) are a class of low molecular weight and cysteine‐rich metal binding proteins present in all the branches of the tree of life. MTs efficiently bind with high affinity several essential and toxic divalent and monovalent transition metals by forming characteristic polynuclear metal‐thiolate clusters within their structure. MTs fulfil multiple biological functions related to their metal binding properties, with essential roles in both Zn(II) and Cu(I) homeostasis as well as metal detoxification. Depending on the organism considered, the primary sequence, and the specific physiological and metabolic status, Cu(I)‐bound MT isoforms have been isolated, and their chemistry and biology characterized. Besides the recognized role in the biochemistry of divalent metals, it is becoming evident that unique biological functions in selectively controlling copper levels, its reactivity as well as copper‐mediated biochemical processes have evolved in some members of the MT superfamily. Selected examples are reviewed to highlight the peculiar chemical properties and biological functions of copper MTs. © 2016 IUBMB Life, 69(4):236–245, 2017